Pathways to Depression: A Multidimensional Composite Analysis of Socioeconomic Inequalities in a Population-Based Study - Wahyu Tri Sudaryanto; Wahyuni; Firmansyah; Afif Ari Wibowo (Masters Program in Public Health, 2026)
Background: Socioeconomic factors are recognized as key contributors to the risk of depression among adults and older populations. However, socioeconomic status (SES) is often measured using single indicators, which may not capture its multidimensional nature. Moreover, the mechanisms through which socioeconomic conditions influence depression remain insufficiently explored. This study aimed to examine the pathways linking socioeconomic inequalities to depression using a multidimensional composite measure of SES. Subjects and Method: A cross-sectional analysis was conducted using data from the 2023 Indonesian Health Survey, a nationally representative population-based survey. SES was constructed using principal component analysis (PCA) based on wealth index, education level, employment status, participation in government social protection programs, and provincial-level income inequality (Gini index). Path analysis was performed to assess direct and indirect relationships between SES, physical activity, comorbidity, and depression. All analyses were conducted using STATA 17. Results: Higher SES was associated with a lower risk of depression. Significant pathways were observed from SES to depression both directly (β= -0.06; 95% CI= -0.07 to -0.06; p <0.001) and indirectly through comorbidity (β= -0.03; 95% CI= -0.03 to 0.02; p <0.001). Conclusion: Socioeconomic inequalities play a critical role in shaping depression risk through multiple pathways.